Improving angle concept understanding at primary school with STY card - Rosita, Hana; Mariana, Neni; Gunansyah, Ganes (IKIP PGRI Bojonegoro, 2025)
The rapid advancement of the times demands that children develop critical thinking skills to solve problems, one of which is by utilizing mathematical concepts, such as angles. However, many elementary school students still struggle to understand the concept of angles, necessitating contextual learning media. One effective approach is integrating regional culture, such as the Jaranan Turonggo Yakso dance. This study aims to describe the effectiveness of STY Cards as a learning medium in enhancing fifth-grade students' understanding of angles at SDN 1 Prigi. The research adopts a descriptive qualitative approach. Data collection techniques include formative assessment results from LKPD (Student Worksheets), interview instruments, and observation instruments. The collected data were analysed using Miles and Huberman's techniques: data reduction, data presentation, and conclusion drawing. The STY Cards guided by the LKPD were effective in improving students' understanding of angles, enabling them to draw angle shapes, identify angle measures, classify angles, and conclude the definitions of various types of angles. The use of STY Cards in group settings also improved students' social skills. The integration of culture into angle learning through STY Cards provides significant benefits for students' daily lives. Students can develop numeracy skills by applying angle concepts to solve problems, such as determining correct posture or alignment, while also contributing to the preservation of regional cultural heritage.